Pesantren dan Millennial Behaviour: Tantangan Pendidikan Pesantren dalam Membina Karakter Santri Milenial - Chusnul Muali; Adi Wibowo; Hambali Hambali; Zaini Gunawan; Immatul Hamimah (At-Tarbiyat, 2020)
This study to determine the challenges of boarding school education in fostering the character of millennial santri at Al-Amanah Islamic Boarding School, which is a boarding school that educates and fosters the character of students. This research uses qualitative research with a type of case study. The informants in this study were the boarding school caretakers, namely the kyai, the ustadz / ustadzah and students in the boarding school environment. The results of the research regarding the challenges that must be faced by students are as follows: first, cultural differentiation. One way of communicating is that the culture and personality of the students are different. Second, the uswah factor. Exemplary and role models for students in Islamic boarding schools. Third. Impact technology. Be aware of advances in technology and information for students so that they are not left behind. Fourth. Double Personality.